2008
DOI: 10.1080/10556780802102586
|View full text |Cite
|
Sign up to set email alerts
|

Classification model selection via bilevel programming

Abstract: Support vector machines and related classification models require the solution of convex optimization problems that have one or more regularization hyper-parameters. Typically, the hyper-parameters are selected to minimize the cross-validated estimates of the out-of-sample classification error of the model. This cross-validation optimization problem can be formulated as a bilevel program in which the outer-level objective minimizes the average number of misclassified points across the cross-validation folds, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 35 publications
0
79
0
Order By: Relevance
“…Recent efforts [30][31][32] have focused on a bilevel optimization approach to implementing K-fold cross-validation. This approach may be beneficial to learn VISHID models by permitting faster SVM model Figure 11.…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts [30][31][32] have focused on a bilevel optimization approach to implementing K-fold cross-validation. This approach may be beneficial to learn VISHID models by permitting faster SVM model Figure 11.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the algorithms presented in this monograph have similar structures. It has already been demonstrated that bilevel machine learning problems perform fairly well with regards to generalization error [3,36] when solved using SQP-based methods such as filter. It should be noted that since the ultimate goal is to produce good generalization, the solutions found need not necessarily be highly accurate or global optimal.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we extend the parameter selection idea introduced in the previous section to support vector classification and show how the bilevel formulation can handle a large number of hyper-parameters; this is a review of work that was first introduced in [36]. The inner-level problem is the standard SVC model [12] augmented with additional feature selection constraints.…”
Section: Parameter Selection For Linear Sv Classificationmentioning
confidence: 99%
See 2 more Smart Citations